Hubungan Pemberian ASI Eksklusif, Status Gizi Dan Personal Hygiene Dengan Kejadian Diare Pada Anak Usia 1-5 Tahun: Relationship Between Exclusive Breastfeeding, Nutritional Status and Personal Hygiene with The Incidence of Diarrhea in Children Aged 1-5 Years - Sity Maryam, Santy (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Diarrhea is a condition in which individuals defecate with a liquid consistency for more than 3 days. Diarrhea disease is still a major problem in the world with high morbidity and mortality rates in many countries. The digestive system can become infected with different bacteria, viruses, and parasites, which can cause diarrhea. Some complications caused by diarrhea include Mild to severe dehydration. Sepsis is a severe infection that can spread to other organs. Malnutrition, especially in children aged less than 5 years, can result in a decrease in the child's immune system. Methods: Quantitative analysis using a cross-sectional design. The population in this study were mothers who had children 1-5 years old who were treated at Dr. Hafiz Hospital Cianjur with a population of 259 people with a total sample of 72 respondents. Determination of the sample using purposive sampling. Results: The results of the relationship between exclusive breastfeeding were found p-value = 0,002 OR = 10,080. Nutritional status p-value = 0,011 OR = 5,897 and Personal Hygiene p-value = 0,002 OR= 7,150. The conclusion is that there is a relationship between exclusive breastfeeding, nutritional status, and personal hygiene with the incidence of diarrhea in children aged 1-5 years at Dr. Hafiz Hospital Cianjur in 2021. The advice is to give children exclusive breastfeeding always pay attention to the nutritional status and keep doing personal hygiene to avoid diarrhea. Discussion: Always try to give exclusive breastfeeding, especially for children aged 0-2 years to provide balanced nutrition and good immunity so that it can prevent children from contracting diseases, especially diseases of digestive problems, besides always paying attention to nutritional conditions to avoid undernutrition conditions and maintain personal hygiene such as always washing hands with water and soap as well as maintaining nail hygiene and always paying attention to the condition of the food or drink that will be consumed.